AN INVESTIGATION INTO THE FAMILY BASED FACTORS INFLUENCING STUDENTS ACADEMIC PERFORMANCE IN PUBLIC SECONDARY SCHOOLS IN MACHAKOS SUB-COUNTY, MACHAKOS COUNTY - MUIYA, PETER M. (My University, 2017)
One of the major aspects of the social pillar of the Kenya Vision 2030 is education. Kenya Vision 2030 points out education and training is an instrument to develop Kenya to be a middle-income economy. Family backgrounds have been highlighted as of great important in molding the performance of children in schools worldwide. This study therefore was to investigate the influence of family based factors on the students academic performance in Machakos sub-county, Machakos County. This study focused on the influences of; parental marital status, family financial status, parents’ education level and family size on the academic performance of students in Machakos sub-county, Machakos County. The study employed a descriptive research design. The target population under the study was the secondary students in Machakos sub-county, Machakos County. The study used a proportionate stratified random sampling method to settle on the sample size. Data was collected by use of questionnaires and interview schedule for students. The data was analyzed quantitatively and qualitatively and presented using frequencies, regression coefficient and Pearson’s coefficient correlation. Statistical Package for Social Sciences was used to aid in generating a summary of results which was represented in a tabular form. The information obtained from the study would be of great importance to parents, school management and the researcher doing research on a similar field.
Keywords: parental marital status